Disfunção craniomandibular e sua correlação com radiografia transcraniana da articulação temporomandibular: estudo comparativo entre indivíduos portadores de sintomas severos pelo índice de helkimo e indivíduos assintomáticos - Takahashi, Fernando Eidi [UNESP] (1997)
Fifty females with ages ranging from 20 to 39 years, were separated in 2 groups of 25, as control and dysfunction group, according to presence or absence of CMD base symptoms, detected at previous interview. Transcranial radiographs were carried out in order to verify condyle position in the mandibular fossa and condyle and fossa forms and contours. Anamnesis and clinical examinations divided groups according to Helkimo Index of CMD and obtained data was cross-classified. Radiographic findings showed an increase of altered condyle positions and altered form and contour of condyles and fossas for dysfunctional group in contrast to control group. No statistical significant differences occurred between groups. The indexes AiO and DiO for control group showed an increased amount of condylar concentricity, a increased number of condyles and mandibular fossas with normal form and contour and less condylar displacements differently than dysfunction group. All females involved in the study presented occlusal disturbances rated by Helkimos Index. Radiographic finding were better translated with the Index of occlusal state